How Different Team Downsizing Approaches Influence Team-Level Adaptation And Performance - DeRue, D. Scott; Hollenbeck, John R.; Johnson, Michael D.; Ilgen, Daniel R.; Jundt, Dustin K. (Academy of Management Journal, 2008)
This study examined the relative effectiveness of three structural approaches to reducing team size. Seventy-one five-person teams engaged in a simulated interactive task in which the approach to downsizing was manipulated. Results suggest that the structural approaches to reducing team size differentially impact team performance, and this relationship is mediated by how and to what degree teams adapt their task-related behaviors. Moreover, results from this study emphasize the importance of team composition in cases of team downsizing. Specifically, emotional stability and extraversion can help mitigate the negative effects associated with reducing team size.